2005
DOI: 10.1124/dmd.105.006031
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Caffeine by CYP1A2: Isotope Effects and Metabolic Switching

Abstract: ABSTRACT:Caffeine (1,3,7-trimethylxanthine) has previously been shown to undergo metabolic switching in vivo when the N-1 or the N-7 methyl groups were trideuteromethylated [Horning et al. (1976) Proceedings of the Second International Conference on Stable Isotopes, pp 41-54]. We have examined the effect of replacing the N-3 methyl group with a trideuteromethyl group. The corresponding isotope effects can then be used to distinguish the kinetic mechanism by which four primary metabolites can be formed from one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In previous studies on sheep and hair goats, it was determined that CF was metabolized to TB, PX and TP (Uney et al, 2011; Uney & Traş, 2011). Also, previous studies have shown that the primary metabolite of CF is TP in sheep (Danielson & Golsteyn, 1996; Uney & Traş, 2011), PX and TP in hairy goats (Uney et al, 2011), and PX in humans (Berthou et al, 1992) and cattle (Danielson & Golsteyn, 1996). Similarly, it is thought that the primary metabolite of CF could be TP that TB and PX could be produced at approximately the same rate at 10 h after administration in Saanen goats.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In previous studies on sheep and hair goats, it was determined that CF was metabolized to TB, PX and TP (Uney et al, 2011; Uney & Traş, 2011). Also, previous studies have shown that the primary metabolite of CF is TP in sheep (Danielson & Golsteyn, 1996; Uney & Traş, 2011), PX and TP in hairy goats (Uney et al, 2011), and PX in humans (Berthou et al, 1992) and cattle (Danielson & Golsteyn, 1996). Similarly, it is thought that the primary metabolite of CF could be TP that TB and PX could be produced at approximately the same rate at 10 h after administration in Saanen goats.…”
Section: Discussionmentioning
confidence: 94%
“…It is the most preferred probe drug in determining the hepatic drug‐oxidizing (metabolic) capacity because it has many features and criteria that an ideal probe drug should carry (Kalow & Tang, 1993). Studies on the determination of the hepatic drug‐oxidizing capacity using CF have been reported in sheep (Uney & Traş, 2011), goat (Uney et al, 2011; Uney & Traş, 2011) and cattle (Danielson & Golsteyn, 1996). However, no information has been found on temporal changes in pregnant goats.…”
Section: Introductionmentioning
confidence: 99%
“…Another source of interference signal might come from to 7β-OH cholesterol, an auto-oxidation products of the cholesterol itself [13, 18, 32]. Although many articles reported that the formation of 7β-OH cholesterol during incubation in an undetectable level [9, 20], one experiment was nevertheless performed to eliminate the potential interference. Cholesterol was incubated in two inactive systems for 1 hour, the boiled microsome with NADPH regenerating system and the normal microsome without NADPH regenerating system.…”
Section: Resultsmentioning
confidence: 99%
“…All microsomes were prepared by standard differential ultracentrifugation [19] with small modification [20]. All the procedures below were done above ice bath in the cold room.…”
Section: Methodsmentioning
confidence: 99%
“…The changes in metabolic pathways are not always predictable and therefore are measured by in vitro and/or in vivo metabolism studies. For example, caffeine deuteration at one methyl group at a time attenuates the oxidation at the deuterated position, whereas it induces significant metabolic switching at the non-deuterated soft spots 34 , 35 . Only per-deuteration of all the three methyl groups ( d 9 -caffeine) (Table 1 ) can effectively reduce N-dealkylation reactions and improve the PK profile 36 , 37 , as judged by a fourfold higher exposure to d 9 -caffeine and a fivefold to tenfold reduced exposure to downstream metabolites relative to unlabelled caffeine in a phase I trial 38 .…”
Section: Possible Benefits Of Deuterium Incorporation In Drugsmentioning
confidence: 99%